PERSEPSI ANGGOTA TENTANG MANFAAT KOPERASI BINA BERSAMA DI DESA JERUJU BESAR KABUPATEN KUBURAYA - Fitri, Fitri; Mashudi, Mashudi; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine members perceptions about the benefits of Bina Bersama cooperatives in Jeruju Besar Village, Kuburaya Regency. The research method used is descriptive method with a form of qualitative research. The data source of this research are members of the Bina Bersama cooperative and the data is the accountability report of the management of the cooperative joint development and the results of interviews with the management and members of the cooperative. The results of the research show that cooperative development has a huge benefit for cooperative members, because some cooperative members feel the benefits of cooperatives. The cooperative provides the remaining business results (SHU) according to the role of the members themselves and is shared fairly. Members get ease in working capital to develop their business, with a mild interest of only 1% after a predetermined maturity. Knowledge is given to members when a member is about to become a member, the management gives direction about the obligations and rights of cooperative members when they become members of the cooperative, so that members can carry out their obligations as active members of this cooperative. The Bina Bersama Cooperative in the village of Jeruju Besar focuses on savings and loans. Members find it easy to save and borrow money from cooperatives.Keywords: Perception, Benefits, Cooperatives